EXPERIMENTAL STUDY ON THE INFLUENCE OF RIBLETS ON BUS BODY TOWARDS DRAG COEFFICIENT - Matthew Sebastian; Fandi D. Suprianto; Teng Sutrisno (Mechanova, 2015)
Heavy vehicles such as buses and trucks, generally have a form that is not very aerodynamic, usuallyvery long and boxy. Aerodynamics can be very influential on the use of fuel when the coefficient ofdrag is reduced, the vehicle can be more efficient in their use of fuel because the force that inhibitswill be reduced. One way to reduce this drag force is with riblets. Riblets is a structure shaped like abunch of lined trenches. The results of the study on flat plate showed that with the riblets, up to 10%drag reduction can be achieved with the blade structure compared with only a flat surface under thesame conditions.Methods to validate the experiments were performed using simulation results with experimentalresults from the wind tunnel at a speed of 16-27 m/s. Bus model created by CAD software accordingto its original shape to be tested in the wind tunnel and then compare it with the results of theANSYS Fluent simulation. Riblets geometry studied using ANSYS Fluent simulation and theresults of the Boundary Layer will be observed as the riblets geometry changes. From the research, itis known that the best riblets geometry is 1% of the overall length of the bus and with the applicationof said geometry, 1.46% drag reduction can be obtained, from Cd 0.548 to 0.54. The model with thebest drag reduction uses riblets on the front roof of the bus.